Trends in Prescription Pain Medication Use by Race/Ethnicity Among US Adults With Noncancer Pain, 2000–2015 - Harrison, Jordan M. (Am J Public Health, 2018)
Objectives. To examine national trends in the use of various pharmacological pain medication classes by race/ethnicity among the US pain population. Methods. We used data from the Medical Expenditure Panel Survey to conduct a nationally representative, serial cross-sectional study of the noninstitutionalized US adult population from 2000 to 2015. We identified adults with moderate or severe self-reported pain and excluded individuals with cancer. We used complex survey design to provide national estimates of the percentage of adults with noncancer pain who received prescription pain medications among 4 groups: non-Hispanic White, non-Hispanic Black, Hispanic or Latino, and other. Results. The age- and gender-adjusted percentage of prescription opioid use increased across all groups, with the greatest increase among non-Hispanic White individuals. By 2015, the percentage of non-Hispanic Black adults using opioids approximated that of non-Hispanic White adults—in 2015, approximately 23% of adults in these 2 groups used opioids. Conclusions. To our knowledge, this is the first evidence of a narrowing divide in opioid prescribing by race. However, in the context of the national epidemic of opioid-related addiction and mortality, opioid-related risks do not appear commensurate with the purported benefits.